Selective recognition of quaternary ammonium ions and zwitterions by using a biomimetic bis-calix[6]arene-based receptor. Issue 42 (18th October 2017) - Moerkerke, Steven; Malytskyi, Volodymyr; Marcélis, Lionel; Wouters, Johan; Jabin, Ivan
Abstract : A biomimetic bis-calix[6]arene binds cationic and zwitterionic species with a high selectivity for carbamylcholine. Abstract : Artificial receptors able to recognize efficiently chemical species bearing a quaternary ammonium group have potential applications in the fields of biological and environmental analyses. A possible biomimetic strategy for the elaboration of such receptors consists of associating in close proximity a polyaromatic cavity with a polar binding site. Herein, we show that bis-calix[6]arene1 behaves as a heteroditopic receptor that can bind biologically relevant quaternary ammonium ions and zwitterions. This host can selectively extract carbamylcholineG3 from water, opening the way for the sensing of this acetylcholine agonist. In some cases, a kinetic selectivity is observed for the shorter guests whereas kinetically stable host–guest complexes can be detected under conditions where they are thermodynamically disfavoured. These results can be rationalized by the unique mode of entrance and escape of the guests into bis-calix[6]arene1 . All these binding properties strongly differ from those reported for related calixarene-based receptors.